Effect of fiber orientation on Liquid–Gas flow in the gas diffusion layer of a polymer electrolyte membrane fuel cell. (1st October 2021) - Lee, Seung-Hun; Nam, Jin Hyun; Kim, Charn-Jung; Kim, Hyung Min
Abstract: In this study, the lattice Boltzmann method was used to simulate the three-dimensional intrusion process of liquid water in the gas diffusion layer (GDL) of a polymer electrolyte membrane fuel cell (PEMFC). The GDL was reconstructed by the stochastic method and used to investigate fiber orientation's influence on liquid water transport in the GDL of a PEMFC. The fiber orientation can be described by the angle between a single fiber and the in-plane direction; three different samples were simulated for three different fiber orientation ranges. The simulated permeability correlated well with the anisotropic characteristics of reconstructed carbon papers. It was concluded that the fiber orientation had a significant effect on the liquid invasion pattern in the GDL by changing the pore shape and distribution of the GDL. The results indicated that the stochastically reconstructed GDL, taking into account the fiber orientation, better demonstrates the mass transport properties of the GDL. Highlights: The LBM was used to simulate dynamic liquid water transport in a PEMFC. The reconstructed 3D GDLs were generated by using the stochastic generation method. Permeability of through- and in-plane was estimated and well represented the anisotropic characteristic of the GDL. The fiber orientation affected the pore structure and significantly influenced the capillary-driven transport in the GDL.